Haemophilia and thrombophilia - Nowak-Göttl, U.; Escuriola, C.; Kurnik, K.; Schobess, R.; Horneff, S.; Kosch, A.; Kreuz, W.; Pollmann, H. (Hämostaseologie, 2003)
For the study presented here 135 pediatric PUP patients with haemophilia consecutively admitted to German pediatric haemophilia treatment centers were investigated. In addition to factor VIII activity, the factor V (FV) G1691A mutation, the factor II (FII) G20210A variant, methylenetetrahydrofolate reductase (MTHFR) T677T genotype, elevated lipoprotein a (Lp a), antithrombin, protein C, and protein S were investigated. 103 out of 122 HA patients (FVIII activity <1%) were suffering from severe HA. The prevalence of prothrombotic risk factors in children with severe haemophilia A (HA) did not differ from previously reported data: FV GA 5.8%, FII GA 3.9%, MTHFR TT 10%, elevated Lp a 7%, protein C type I deficiency 1.1%. The first symptomatic bleeding leading to diagnosis of severe haemophilia occurred with a median age of 1.6 years (range: 0.5-7.1 years) in children carrying prothrombotic risk factors compared to non-carriers (0.9 years (0.1-4.0; p = 0.01). Two patients presenting with neonatal stroke due to elevated Lp a and the FII GA variant showed haemorrhagic stroke transformation triggered by severe haemophilia. In addition, when haemophilia A was corrected by administration of factor VIII concentrates eight out of 25 children with central lines in place developed catheter-related thrombosis. Conclusion: The data of this multicentre cohort study demonstrate that the clinical phenotype of severe haemophilia A in childhood is clearly influenced by the coinheritance of prothrombotic risk factors.
Keywords: Severe haemophilia A; pediatric PUP patients; factor V G1691A; factor II G20210A